Combined 15N-Labeling and TandemMOAC Quantifies Phosphorylation of MAP Kinase Substrates Downstream of MKK7 in Arabidopsis - Huck, Nicola V.; Leissing, Franz; Majovsky, Petra; Buntru, Matthias; Aretz, Christina; Flecken, Mirkko; Müller, Jörg P. J.; Vogel, Simon; Schillberg, Stefan; Hoehenwarter, Wolfgang; Conrath, Uwe; Beckers, Gerold J. M. (Frontiers in Plant Science, 2017)
Reversible protein phosphorylation is a widespread posttranslational modification that plays a key role in eukaryotic signal transduction. Due to the dynamics of protein abundance, low stoichiometry and transient nature of protein phosphorylation, the detection and accurate quantification of substrate phosphorylation by protein kinases remains a challenge in phosphoproteome research. Here, we combine tandem metal-oxide affinity chromatography (tandemMOAC) with stable isotope 15N metabolic labeling for the measurement and accurate quantification of low abundant, transiently phosphorylated peptides by mass spectrometry. Since tandemMOAC is not biased towards the enrichment of acidophilic, basophilic or proline-directed kinase substrates, the method is applicable to identify targets of all these three types of protein kinases. The MKK7-MPK3/6 module, for example, is involved in the regulation of plant development and plant basal and systemic immune responses, but little is known about downstream cascade components. Using our here described phosphoproteomics approach we identified several MPK substrates downstream of the MKK7-MPK3/6 phosphorylation cascade in Arabidopsis. The identification and validation of dynamin-related protein 2 as a novel phosphorylation substrate of the MKK7-MPK3/6 module establishes a novel link between MPK signaling and clathrin-mediated vesicle trafficking.